Wirth, "Mountains, Rivers, and the Great Earth: Reading Gary Snyder and Dōgen in an Age of Ecological Crisis" - Shepherd, Kelly (The Trumpeter, 2021)
A book review of Mountains, Rivers, and the Great Earth: Reading Gary Snyder and Dōgen in an Age of Ecological Crisis by Jason M. Wirth, published by State University of New York Press (2017).